Seven wonders of the industrial world - BBC worldwide ([Australia : BBC Worldwide, 2003)
An encounter with the most brilliant pioneers of the industrial age. Recreating their stories of burning ambition, extravagant dreams, passion and rivalry as great minds clashed, this programme delves into the history of seven epic monuments spanning the industrial revolution
ep. 1. The great ship -- ep. 5. The Panama Canal
Title from added title page title
Executive producer,Jill Fullerton Smith ; written and directed by Christopher Speneer (ep.1) ; produced and directed by Philip Smith (ep.5)
Narrator: Robert Lindsay
DVD Format
Keywords: Civil engineering -- History -- 19th century